ANALISIS KREATIVITAS PADA PELAKSANAAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA BERBASIS KEARIFAN LOKAL KAOS JUMPUTAN SDN 1 PURBALINGGA LOR - Prasetiyo, Hanjar Agung; Wijayanti, Okto (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to analyze local wisdom-based creativity through tie-dye (jumputan) t-shirt projects at SDN 1 Purbalingga Lor in implementing the Pancasila Student Profile (P5) strengthening program. The research employed a descriptive qualitative approach using phenomenology to understand the phenomenon experienced by the subjects in a specific context. Data were collected through observation, interviews, and documentation, and analyzed through data collection, reduction, presentation, and conclusion drawing. The results indicate that P5 learning in grade IV introduces students to local wisdom, specifically tie-dye t-shirts, as part of the Merdeka Curriculum designed to develop students’ character in line with the Pancasila Student Profile, particularly in the creative dimension. The study concludes that implementing P5 projects based on local wisdom can serve as an effective strategy to foster students’ creativity.